Length–Weight Relationships of the Prized Sea Cucumber Holothuria lessoni from In Situ and Ex Situ Measurements - Lea A. F. Djenidi; Steven W. Purcell; Aaron W. Thornton; Hugues Gossuin; Antoine Gilbert (Journal of Marine Science and Engineering)
Fisheries science draws on morphometric data for stock assessments. Length–weight relationships are essential for estimating body weight from length measurements taken either underwater (in situ) or out of the water (ex situ). We examined morphometric models for the high-valued sea cucumber, Holothuria lessoni. From 77 specimens captured in 2024 (mean weight ± SD: 1774 ± 372 g), we measured body length and width in situ and ex situ, then weighed the animals ex situ. We compared morphometric models using four biometric parameters. The fitted relationships were more statistically significant (p < 0.001) when using in situ measurements compared to ex situ measurements. The length–weight relationship from our study was compared with those from two previous studies on the same species at the same location. Each study generated significantly (p < 0.001) different length–weight relationships. These findings suggest that length–weight relationships should be re-evaluated at regular intervals, as they may evolve over time. Our study indicates that estimation of body weight from length (and width) must rely on established relationships corresponding to whether the measurements are made in situ or ex situ. Our results suggest that in situ measurements could provide more reliable data for length–weight relationships in certain holothuroids.